Mechanical design of a low-cost ABS hand prosthesis using the finite element method - Bastarraceha, Aztlán; Estrada Barbosa, Quirino; Torres, Vianey; Reynoso Jardón, elva; Zubrzycki, J; Rodríguez-Mendez, A; Coutiño, E (2021)
Many hand accidents are reported around the world resulting in a necessity to perform a procedure of amputation of the hand. For this consideration, a large number of hand prostheses have been designed. However, the mechanical design of these prostheses present challenges such as kinematic functionality, strength, and cost. The present article analyses the mechanical design of a low-cost practical hand prosthesis using the finite element method with the help of Abaqus commercial software. Functional and technical requirements were considered to consider the biomechanics of the human hand. The hand prosthesis was conferred with 14-degrees-of-freedom (DOF), which gives it the capacity for grips associated with security, stability, dexterity, and sensibility. Additionally, due to practicality and low-cost manufacturing techniques, fused deposition modelling with acrylonitrile butadiene styrene (ABS) is proposed. The evaluation of the hand prosthesis was carried out by tensile, flexural, and torsional load conditions. Finally, the mechanical effectiveness of the designed prosthesis was demonstrated since maximum stresses close to 13 MPa were computed, which are less than the yield stress of ABS.